SOCIALIZATION OF INQUIRY LEARNING STRATEGIES IN ELEMENTARY SCHOOL LEARNING - Sukardo Sitohang; Minar Trisnawati Tobing; Radode Kristianto Simarmata; Eva Pasaribu (RADJA PUBLIKA, 2024)
This socialization activity aims to describe the implementation and impact of the socialization of inquiry learning strategies in elementary school learning. This socialization activity was given to 10 teachers who teach at SD Negeri 017107 Kisaran Naga, Asahan Regency, and was carried out for two days, namely on Friday and Saturday, August 4 and 5, 2023. The inquiry learning strategy was introduced as an approach that emphasizes the active involvement of students in the learning process through asking, questioning, and drawing based on evidence. The methods used in this activity were interactive lectures, group discussions, and the practice of preparing inquiry-based lesson plans. The results of the activity showed that teachers began to understand the importance of implementing inquiry learning to improve students' critical and creative thinking skills. In addition, the participants also showed high enthusiasm in designing more student-centered learning activities. This socialization has positive implications for changes in teachers' mindsets and teaching practices, although challenges such as limited time and facilities are still being found. Therefore, follow-up in the form of ongoing mentoring and further training is needed so that the inquiry learning strategy can be implemented optimally in daily learning in elementary schools.